Comparative study on the efficacy of different aflibercept regimens in the treatment of macular edema secondary to branch retinal vein occlusion - Du, Xing; Guo, Yuanyuan; Du, Min; Wang, Wen; Liu, Mingkun; Li, Shanshan; Sheng, Yanjuan (Frontiers in Medicine, 2025)
ObjectivesTo compare the efficacy of intravitreal injection of aflibercept between the treat-and-extend (TAE) and pro re nata (PRN, as needed) regimens in the treatment of macular edema secondary to branch retinal vein occlusion, to determine the best regimen in terms of efficacy.MethodsThis was a retrospective case–control study. Totally 62 eyes in 62 patients diagnosed with macular edema secondary to branch retinal vein occlusion (BRVO-ME) from January 2018 to September 2021 were subjected to intravitreal injection of aflibercept according to the different regimens, including the TAE and PRN groups (32 and 30 in the TAE and PRN groups, respectively). Baseline characteristics including age, gender, affected eyes, best corrected visual acuity (BCVA), and central retinal thickness (CRT) were reviewed. The number of injections, number of visits, as well as BCVA and CRT after 12 months of treatment were collected and compared between two groups.ResultsBCVA was 60.7 ± 7.6 and 59.9 ± 6.1 letters at first diagnosis, and 82.1 ± 6.1 and 78.1 ± 5.8 letters after 12 months of treatment in the TAE and PRN groups, respectively. All BCVA was significantly improved from baseline (p < 0.01). Based on between-group comparison, BCVA was significantly higher in the TAE group compared with the PRN group (p < 0.05). CRT was 483.0 ± 121.5 μm and 478.4 ± 113.0 μm at first diagnosis, and 249.9 ± 30.7 μm and 302.4 ± 41.1 μm after 12 months of treatment in the TAE and PRN groups, respectively. All CRT was substantially reduced from baseline (p < 0.01). Based on between-group comparison, CRT was significantly lower in the TAE group compared with the PRN group (p < 0.05). The average numbers of visits were 8.6 and 11.5 in the TAE and PRN groups, respectively, indicating a statistically significant difference (p < 0.01). The average numbers of injections were 7.6 and 8.1 in the TAE and PRN groups, respectively, with a statistically significant between-group difference (p < 0.05).ConclusionThe TAE regimen is superior to the PRN regimen in terms of efficacy for aflibercept administration in macular edema secondary to branch retinal vein occlusion, with the former regimen also associated with reduced number of injections and visits, as well as decreased burden on patients and physicians.